Scanning Electron Microscopy of Antennae and Mouthparts of Mezira yunnana Hsiao (Hemiptera: Aradidae): Specialized Microstructures Reflecting Adaptation to Mycetophagy - Shiyu Zha; Zhiyao Wang; Li Tian; Yisheng Zhao; Xiaoshuan Bai; Zhaoyang Chen; Wanzhi Cai; Xinyu Li; Hu Li (Insects, 2023)
Many species of the family Aradidae (also known as flat bugs) feed on fungal mycelia and fruiting bodies. In order to better understand the morphological adaptation to this unique feeding habit, we examined the microstructure of antennae and mouthparts of an aradid species, Mezira yunnana Hsiao, using scanning electron microscope, and documented the fungal feeding process under laboratory conditions. The antennal sensilla include three subtypes of sensilla trichodea, three subtypes of sensilla basiconica, two subtypes of sensilla chaetica, sensilla campaniformia, and sensilla styloconica. The apex of the second segment of flagellum has a large number of various sensilla forming a sensilla cluster. The labial tip is distally constricted, which is rarely observed in other Pentatomomorpha species. The labial sensilla include three subtypes of sensilla trichodea, three subtypes of sensilla basiconica, and a sensilla campaniformia. The tip of the labium has only three pairs of sensilla basiconica III and small comb-shaped cuticular processes. The external surface of the mandibular apex has 8–10 ridge-like central teeth. A series of key morphological structures associated with mycetophagous feeding habit were identified, which will facilitate future studies on adaptive evolution of species in Pentatomomorpha as well as in other heteropteran lineages.